Perkembangan dan Pelaksanaan Lembaga Wakaf di Negara Sekuler (Singapura dan Thailand) - Saputra, Iin; Brilliyandra, Fradini; S, Syahpawi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The comparison between Singapore and Thailand in terms of the development and implementation of waqf institutions is interesting to explore. The two countries have different approaches to waqf management, both in terms of regulations and practical application in the field. Writing this paper can provide valuable insight into how secular countries can facilitate waqf institutions within the applicable legal and policy framework. In addition, further exploration of the contribution of waqf in the development of Muslim societies in these secular countries can provide a clearer picture of the resulting social and economic impacts. This can also help strengthen regional cooperation in the field of sharia finance and encourage inclusive economic growth in the Southeast Asia region. This research is a literature study with a qualitative approach to look at the development and implementation of waqf institutions in Singapore and Thailand. The main data source in this research is from written sources that are directly related to the research. In data analysis, the author uses qualitative analysis by coding data, reducing data, and drawing conclusions. The research results show that the history of waqf in Singapore began with the initial founding of the country by immigrants from Hadramaut, Yemen. Meanwhile, in Thailand, waqf is managed independently by families and communities without any special state regulations. Waqf management in Singapore is handled by Muis Ugama Islam Singapura (Muis), which acts as a legal and supervisory body. In Thailand, waqf management is managed by Chularajmontri, the Provincial Committee for Islamic Affairs, and the Mosque Committee, which play a role in managing waqf properties. Waqf administration in Singapore is more structured and regulated by Muis. In Thailand, waqf management is more community and family in nature, facing challenges related to professional expertise and innovation in waqf development.